EFFICACY AND SAFETY OF CYCLOPHOSPHAMIDE LOW-DOSE PRE-PHASE CHEMOTHERAPY IN DIFFUSE LARGE B CELL LYMPHOMA WITH GASTROINTESTINAL INVOLVEMENT - Luca Guarnera; Federico Meconi; Roberto Secchi; Maria Rosaria Pascale; Fabiana Esposito; Annagiulia Zizzari; Vito Mario Rapisarda; Manuela Rizzo; Livio Pupo; Maria Cantonetti (Mediterranean Journal of Hematology and Infectious Diseases)
Introduction Gastric Diffuse large B‐cell lymphoma (DLBCL) is the most common extra-nodal site of lymphoma’s involvement (30%-40% of all extranodal lymphomas and 55%-65% of all gastrointestinal lymphomas). However, gastric localizations are also sometimes found in systemic DLBCL. Gastric complications such as bleeding, perforation and stenosis under chemotherapy are well documented.  Methods We retrospectively analyzed 15 patients with newly diagnosed DLBCL with gastrointestinal involvement. Endoscopies were performed in these patients before and after treatment. Treatment consisted in cyclophosphamide low-dose pre-phase chemotherapy before conventional-dose chemotherapy. Results Endoscopy at staging detected ulcers in 12 patients (80%). After low-dose pre-phase chemotherapy GI ulcers healed in 91.6% of cases (1 ulcer detected). After the whole treatment (Low-dose pre-phase + chemotherapy) 9 patients (60%) achieved complete response, 4 patients (26.6%) partial response, 2 (13,3%) patients presented disease progression. The most frequent adverse event was neutropenia (73.3%); the most frequent non hematological adverse event was transaminases elevation (20%). Conclusion Cyclophosphamide low-dose pre-phase chemotherapy resulted a safe and effective way to prevent adverse events in systemic DLBCL with gastrointestinal involvement.